Penetapan Kadar Logam Timbal (Pb) Pada Air Minum Isi Ulang Di Sekitar Kampus Sekolah Tinggi Ilmu Farmasi (Stifar) Riau Secara Spektrofotometri Serapan Atom (Ssa) - Sintia Nanda Meilani (Jurnal Penelitian Farmasi Indonesia)
Research has been conducted on the determination of lead metal content (Pb) in refill drinking water around the campus of the Riau Pharmaceutical Sciences College (STIFAR) by Atomic Absorption Spectrophotometry (SSA) with the aim to determine the metal content of lead (Pb) in refill drinking water in around the campus of the Riau Pharmaceutical Sciences College (STIFAR). The results showed that Pb metal content in the four samples of refill drinking water ranged from 0.11 to 0.19 mg / L. Based on the results of the study, lead metal (Pb) from the four samples of refill drinking water passed the maximum level and did not meet the requirements of drinking water quality according to the Regulation of the Minister of Health of the Republic of Indonesia No. 492 / MENKES / PER / IV / 2010 which is not more than 0.01 mg / L.